Comparison of the clinical outcomes between conventional intracytoplasmic sperm injection (ICSI) and PIEZO-ICSI in women undergoing the first cycle of in-vitro fertilization - Chun Kyu Lim; Sun Hee Shin; Go-woon Kim; Hwa Yeong Kim; Hye Jin Cha; Jung Jae Ko; Kyung-Ah Lee; Hyejin Ryu; Kyung Eun Lee; Seyul Han; Wonyun Choi (PLoS ONE, 2025)
The effectiveness of PIEZO-ICSI (P-ICSI) compared to conventional ICSI (C-ICSI) is still controversial. The only confirmed effectiveness of P-ICSI compared to C-ICSI is that it can reduce the number of degenerated oocytes after ICSI. This study included 100 patients undergoing their first IVF cycle. The patients were randomly assigned to C-ICSI group and P-ICSI group, 50 patients per each group. A total of 2,434 oocytes were retrieved from 100 patients. Among them, 1,527 oocytes with visible meiotic spindle were inseminated by C-ICSI or P-ICSI (778 by C-ICSI, 749 by P-ICSI). Fertilization, degeneration after ICSI and blastocyst development were compared between the C-ICSI group and P-ICSI group. Among the embryos developed to blastocysts, good quality blastocysts were vitrified. The frozen-thawed embryo transfer (FET) cycles were carried out in 42 patients of C-ICSI group and in 45 patients of P-ICSI group. Clinical pregnancy outcomes were analyzed. The differences between C-ICSI group and P-ICSI group were statistically analyzed using Mann-Whitney U test or chi-Square test. Patient age was not different between C-ICSI group and P-ICSI group (33.5 ± 2.7 vs. 32.9 ± 2.4, P = 0.12114). Normal fertilization rate of P-ICSI group (584/749, 78.0%) was significantly higher than that of C-ICSI group (565/778, 72.6%, P = 0.0176). The oocyte degeneration rate after ICSI was significantly higher in C-ICSI group (49/778, 6.3%) than in P-ICSI group (24/749, 3.2%, P = 0.0055). Among the fertilized oocytes, 21 did not cleave; 14 were from C-ICSI group (2.48%) and 7 from P-ICSI group (1.20%, P = 0.1250). Blastocyst formation rate (65.5% vs. 67.8%, P = 0.4485) and the rates of blastocyst that were available for vitrification (59.3% vs. 62.6%, P = 0.2724) were not different between C-ICSI group and P-ICSI group. Blastocyst formation rate on day 5 was significantly higher in P-ICSI group (50.3%) than in C-ICSI group (43.9%, P = 0.0367). In FET cycles, average age of patients was 33.6 ± 2.6 years old in C-ICSI group and that was 32.9 ± 2.3 years old in P-ICSI group. The average number of transferred embryos was 1.5 ± 0.5 in C-ICSI group and 1.2 ± 0.4 in P-ICSI group. The clinical pregnancy rate and the abortion rate of C-ICSI group were 64.3% and 18.5%, respectively. Those of P-ICSI group were 66.7% and 23.3%, respectively. This study showed that normal fertilization rate, the survival of oocytes after ICSI and blastocyst formation rate on day 5 were significantly higher in P-ICSI group than in C-ICSI group. Developmental arrest of zygotes was lower in P-ICSI group than in C-ICSI group. The number of embryos available for vitrification can be increased by implementing P-ICSI. P-ICSI has the potential to improve the development of zygotes into blastocysts.